Spatial Updating Depends on Gravity - Stahn, Alexander Christoph; Riemer, Martin; Wolbers, Thomas; Werner, Anika; Brauns, Katharina; Besnard, Stephane; Denise, Pierre; Kühn, Simone; Gunga, Hanns-Christian (Frontiers in Neural Circuits, 2020)
As we move through an environment, the positions of surrounding objects relative to our body constantly change, with some objects even leaving the field of view. Hence, maintaining orientation requires spatial updating, the continuous monitoring of self-motion cues to update external locations. This ability critically depends on the integration of visual, proprioceptive, kinesthetic, and vestibular information. During weightlessness, however, gravity no longer acts as an essential reference, creating a discrepancy between vestibular, visual and sensorimotor signals. Here we explore the effects of repeated bouts of weightlessness on spatial updating performance using parabolic flight. Ten healthy participants (4 women, 6 men) took part in a parabolic flight campaign that comprised a total of 31 parabolas. Each parabola created about 20 to 25 s of 0 g, preceded and followed by about 20 s of hypergravity (1.8 g). Each participant performed a visual spatial updating task in seated position during 15 parabolas. Two trials were performed during each phase of the parabola, i.e., at 1 g before the start of the parabola, at 1.8 g during the acceleration phase of the parabola, and during 0 g. We show that 0 g and 1.8 g impaired pointing performance for long updating trials as indicated by increased variability of pointing errors compared to 1 g. In contrast, we found no support for any changes for short updating and static condition, suggesting that a certain degree of task complexity is required to affect pointing errors. These findings confirm our hypothesis that gravity affects distinctive cognitive domains that rely on vestibular afferents. Our results demonstrate the role of gravity for spatial updating. Given that spatial updating is vital for navigation when vision is poor or unreliable and objects go out of sight, for example during extravehicular activities during spaceflight operations and exploration of unfamiliar planets, further research on spatial updating performance and other distinct aspects of spatial navigation during altered gravity conditions is critical for future long-duration space missions. Future studies should compare the effects of pointing error during seated and free-floating conditions, and determine at which g-threshold decrements in spatial updating performance emerge.